Experimental and Numerical investigation of Heat transfer enhancement using Al2O3-Ethylene Glycol/Water Nanofluids in Straight Channel - Mohammed, K. Mohammed; M. Kh., Abdolbaqi; Ibrahim, Thamir K.; R., Mamat; Awad, Omar I. (2016)
A study of computational fluid dynamics has been conducted to study the characteristics of the heat transfer and friction factor of Al2O3/Ethylene glycol-water nanofluid flowing in straight channel. The three dimensional realizable k– turbulent model with enhanced wall treatment was utilized. As well as were used Temperature dependent thermophysical properties of nanofluid and water. The evaluation of the overall performance of the tested channel was predicated on the thermo-hydrodynamic performance index. The obtained results showed that the difference in behaviour depending on the parameter that has been selected to compare the nanofluid with the base fluid. In addition, the friction factor and the heat transfer coefficient increases with an increase of the nanoparticles volume concentration at the same Reynolds number. The penalty of pressure drop is negligible with an increase of the volume concentration of nanoparticles. Conventional correlations that have been used in turbulent flow regime to predict average heat transfer and friction factor are Dittus-Boelter and Blasius correlations, for channel are also valid for the tested nanofluids which consider that the nanofluids have a homogeneous fluid behave.